Breakthrough COVID-19 in vaccinated patients with hematologic malignancies: results from the EPICOVIDEHA survey - Pagano, Livio; Salmanton-García, Jon; Marchesi, Francesco; Blennow, Ola; Gomes da Silva, Maria; Glenthøj, Andreas; van Doesum, Jaap; Bilgin, Yavuz M; López-García, Alberto; Itri, Federico; Nunes Rodrigues, Raquel; Weinbergerová, Barbora; et al. (Blood, 2022)
Limited data are available on breakthrough COVID-19 in patients with hematologic malignancy (HM) after anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination. Adult patients with HM, ≥1 dose of anti-SARS-CoV-2 vaccine, and breakthrough COVID-19 between January 2021 and March 2022 were analyzed. A total of 1548 cases were included, mainly lymphoid malignancies (1181 cases, 76%). After viral sequencing in 753 cases (49%), the Omicron variant was prevalent (517, 68.7%). Most of the patients received ≤2 vaccine doses before COVID-19 (1419, 91%), mostly mRNA-based (1377, 89%). Overall, 906 patients (59%) received COVID-19-specific treatment. After 30-day follow-up from COVID-19 diagnosis, 143 patients (9%) died. The mortality rate in patients with the Omicron variant was 7.9%, comparable to other variants, with a significantly lower 30-day mortality rate than in the prevaccine era (31%). In the univariable analysis, older age (P < .001), active HM (P < .001), and severe and critical COVID-19 (P = .007 and P < .001, respectively) were associated with mortality. Conversely, patients receiving monoclonal antibodies, even for severe or critical COVID-19, had a lower mortality rate (P < .001). In the multivariable model, older age, active disease, critical COVID-19, and 2-3 comorbidities were correlated with a higher mortality, whereas monoclonal antibody administration, alone (P < .001) or combined with antivirals (P = .009), was protective. Although mortality is significantly lower than in the prevaccination era, breakthrough COVID-19 in HM is still associated with considerable mortality. Death rate was lower in patients who received monoclonal antibodies, alone or in combination with antivirals.
Keywords: Antibodies, Viral; monoklonální protilátky; testování na COVID-19; protilátky virové; COVID-19; COVID-19 Testing; Hematologic Neoplasms; lidé; hematologické nádory; Adult; Antiviral Agents; antivirové látky; dospělí; Humans; Antibodies, Monoclonal; SARS-CoV-2